Van uw tijd ? Kunstgrepen omtrent 58 - De Boodt, Kurt; Geirlandt, Karel J. (Mechelen : Hof van Busleyden Mechelen Stedelijke Musea Mechelen, 2008)
Anthoons, Willy ; Beeck, Joz. ; Burssens, Jan ; Callewaert, Marc ; De Vree, Paul ; Dries, Jan ; Fontana, Lucio ; Gard, Sivik ; Gentils, Vic ; Gilles, Ray ; Hendrickx, Alfred ; Kuper, Jan ; Laenen, Jean-Paul ; Manzoni, Piero ; Melens, Theo ; Meysmans, Willy ; Michiels, Ivo ; Raes, Hugo ; Seuphor, Michel ; Strebelle, Olivier ; Brande, Frans Van Den ; Vandenbranden, Guy ; Auwera, Stella Van Der ; Van Hoeydonck, Paul ; Van Itterbeek, August ; Van Itterbeek, Ferdinand ; Van Severen, Dan ; van Vlasselaer, Julien Jean ; Verheyen, Jef ; Verstockt, Mark ; Walravens, Frans ; Walravens, Jan ; Zero
biog. per kunstenaar
Nederlands
Exhibition. Van uw tijd ? Kunstgrepen omtrent 58. Mechelen. Hof van Busleyden Mechelen, 11 oktober 2008 - 11 januari 2009
boek